Profiles in caregiving : the unexpected career - Aneshensel, Carol S. (Academic Press, 1995)
Given medical advances and greater understanding of healthful living habits, people are living longer lives. Proportionally speaking, a greater percentage of the population is elderly. Despite medical advances, there is still no cure for dementia, and as elderly individuals succumb to Alzheimer's Disease or related dementia, more and more people are having to care their elderly parents and /or siblings. Profiles in Caregiving is practical source of information for anyone who teaches caregiving, acts as a caregiver, or studies caregiving. This book discusses recent research on stress factors as.